Thermosetting resin composition and application thereof
Through the use of cured polysthenylene ether resin and multi -aggressive double Malayamide resin, combined with specific process treatment in thermal resin composition, combined with specific process treatment, the existing resin products are solved. The problem of processing defects realizes the low -expansion coefficient and low -agency electrical performance suitable for high -frequency and high -speed copper -covering plates.
Patent Information
- Application Number
- CN202411477767.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-25
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
AI Technical Summary
At this stage, when resin products based on modified polyphenylene ether (MPPO) achieve low thermal expansion coefficient (CTE), a higher proportion of fillers need to be added, resulting in processability defects and cannot meet the needs of high-frequency and high-speed copper clad plates.
Provide a thermal resin composition, including solidified polysthenylene ether resin, multi -agentic cannicide resin, benzene -containing or hybrid ethylene counters, nuclear shell rubber, flame retardant, filler, promoter agent, promoter agent , Ethylene -containing Silicane coupling agents and solvents, through specific proportion and process treatment, regulate the molecular weight and cross -linking density of the resin to achieve the low XY axis expansion coefficient and low -agent electricity performance.
The extremely low XY axis expansion coefficient, dielectric constant and dielectric loss, strong heat resistance and excellent processingability, suitable for high -frequency and high -speed copper -covered plate production, which meets the high standards and strictness of high -frequency and high -speed eras. Require.
Smart Images

Figure CN119350835A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polyphenylene ether resin, and in particular to a thermosetting resin composition, a prepreg and a printed circuit board. Background Art
[0002] Among the raw materials for the production of copper clad laminates, thermosetting resins such as epoxy resins, cyanate esters and polyimides are more suitable as matrix resin materials. Among them, epoxy resin is the most widely used. However, although the types of epoxy resins used in copper clad laminate substrates are different, the shortcomings of epoxy resins are still unavoidable, such as high dielectric loss and dielectric constant, poor thermal stability and thermal conductivity, which determines that epoxy resins are only suitable for low-frequency and low-speed fields. The disadvantages of cyanate esters and polyimides are that they are difficult to process and have high requirements. In addition, the common shortcomings of the above-mentioned resins are that the dielectric constant and dielectric loss are not low enough.
[0003] With the rapid development of the fifth generation mobile communication technology (5G), low dielectric constant materials suitable for high-frequency and high-speed information transmission have also become the main research and development direction of printed circuit boards. Among various polymer materials, polyphenylene ether resin has a low dielectric constant and low dielectric loss due to its highly symmetrical rigid main chain structure, which is very consistent with the requirements of copper clad laminate substrates for resins. However, polyphenylene ether itself is a thermoplastic resin and cannot be directly applied to copper clad laminates. Therefore, it is often prepared into modified polyphenylene ether (MPPO) or added to other types of matrix resins to meet usage requirements.
[0004] It has been found that the high-frequency and high-speed copper-clad laminates under the new generation of communication technology have higher requirements on the thermal expansion coefficient of the material. If the thermal expansion coefficients between the semiconductor components and the substrate are too different, the difference in thermal expansion coefficients will easily cause the substrate to warp under heating conditions, resulting in serious problems such as poor connection between the semiconductor components and the substrate, and between the substrate and the PCB.
[0005] At present, the performance of MPPO-based resin products usually has a large XY-axis expansion coefficient. To achieve a low expansion coefficient, the content of fillers in the resin products needs to be increased. The current method to achieve low CTE is to add a higher proportion of fillers, which should be added to 60%-75% by mass. Too much filler addition will lead to processing defects, such as poor filling, excessive drilling wear, etc., which cannot be used for high-frequency and high-speed copper clad laminates. Summary of the invention
[0006] In order to overcome the technical problem that the current MPPO-based resin products cannot achieve both low expansion coefficient and low dielectric properties, a thermosetting resin composition and its application are provided.
[0007] In order to solve the above problems, the present invention is implemented according to the following technical solutions:
[0008] In a first aspect, the present invention provides a thermosetting resin composition, wherein the thermosetting resin composition comprises the following raw materials in parts by weight:
[0009] 20-50 parts of curable polyphenylene ether resin;
[0010] 10-30 parts of multifunctional bismaleimide resin;
[0011] Containing 30-70 parts of benzene ring or heterocyclic vinyl crosslinking agent;
[0012] 1 to 15 parts of flame retardant;
[0013] 100-150 parts of filler;
[0014] Accelerator 0.1-1 part;
[0015] 0.1 to 1 part of vinyl-containing silane coupling agent;
[0016] 50 to 100 parts of solvent.
[0017] In combination with the first aspect, the present invention further provides a first preferred implementation of the first aspect. Specifically, the structural formula of the curable polyphenylene ether resin is:
[0018]
[0019] Wherein, both R1 and R2 are curable functional groups containing a biphenyl structure, and the number average molecular weight of the curable polyphenylene ether resin is 800 to 1400 g / mol.
[0020] In combination with the first aspect, the present invention further provides a second preferred embodiment of the first aspect, specifically, R1 and R2 in the structural formula of the curable polyphenylene ether resin are independently selected from structural formula I or structural formula II;
[0021] Structural formula I is:
[0022]
[0023] Structural formula II is:
[0024]
[0025] In the above structural formula I and structural formula II, R3, R4, R7, and R8 are each independently selected from a hydrogen group or a methyl group; R5, R6, R9, and R10 are each independently selected from a hydrogen group or a vinyl group;
[0026] Among them, R5 and R6 are located at the ortho, meta or para position of the benzene ring, and R5 and R6 contain at least one vinyl group; R9 and R10 are located at the ortho, meta or para position of the benzene ring, and R9 and R10 contain at least one vinyl group.
[0027] In combination with the first aspect, the present invention further provides a third preferred implementation of the first aspect. Specifically, the structural formula of X in the structural formula of the curable polyphenylene ether resin is:
[0028]
[0029] The n is selected from an integer of 1-50, and the m is selected from an integer of 1-50.
[0030] In combination with the first aspect, the present invention further provides a fourth preferred embodiment of the first aspect, specifically, the multifunctional bismaleimide resin includes a bismaleimide monomer having at least three functional groups.
[0031] In combination with the first aspect, the present invention also provides a fifth preferred implementation of the first aspect, specifically, the benzene ring or heterocyclic vinyl cross-linking agent is divinylbenzene, 4,4'-divinylbiphenyl, 4,4'-diallyl-1,1'-biphenyl, vinyl norbornene, 2,2-diallyl-4,4'-biphenol, and at least two of an unsaturated styrene-butadiene copolymer having a number average molecular weight of 800 to 2000 g / mol, triallyl isocyanate and vinyl phosphazene.
[0032] In combination with the first aspect, the present invention also provides a sixth preferred implementation manner of the first aspect, specifically, the filler includes nano-spherical silicon and micron-spherical silicon, the nano-spherical silicon accounts for 5% to 30% of the total weight of the filler, and the micron-spherical silicon accounts for 70% to 95% of the total weight of the filler.
[0033] In combination with the first aspect, the present invention further provides a seventh preferred implementation of the first aspect, specifically, the thermosetting resin composition further comprises 0 to 6 parts by weight of core-shell rubber.
[0034] In a second aspect, the present invention further provides a method for preparing the thermosetting resin composition of the first aspect, the preparation method comprising the following steps:
[0035] Step (1): dissolving the single-terminal polyphenylene ether PPO-OH in a solvent, stirring to obtain a solution, adding an initiator, a phenolic compound and an inhibitor to the solution for reaction; wherein the reaction temperature is 70 to 80° C., the reaction time is 5 to 7 hours, after the reaction is completed, precipitating with a poor solvent for the polyphenylene ether, and then filtering and washing to obtain the double-terminal hydroxyl polyphenylene ether PPO-2OH;
[0036] Wherein, the molecular structural formula of the phenolic compound is
[0037]
[0038] Step (2): at 60° C., dissolving the double-terminated hydroxyl polyphenylene ether PPO-2OH obtained in step (1) in toluene to obtain a polyphenylene ether solution, stirring, adding dichloromethane to a 10 wt % NaOH solution to obtain an alkaline solution; then, in a nitrogen environment, adding the alkaline solution to the polyphenylene ether solution for reaction for 0.5 h, and then adding tetrabutylammonium bromide; finally, slowly adding a dichloromethane solution containing a capping agent to the polyphenylene ether solution for reaction; extracting the product after the reaction with ethanol for 4 to 5 times, and then filtering and vacuum drying for 10 h to obtain a vinyl-terminated biphenyl curable polyphenylene ether;
[0039] Wherein, the molecular structural formula of the end-capping agent is
[0040] In step (2), when the end-capping agent is a structural band The reaction time is 3h, and the reaction temperature is 25℃; when the end-capping agent is selected from the structural band The reaction time is 6 hours, and the reaction temperature is 60°C;
[0041] Wherein, the solvent is at least one of benzene, toluene, dichloromethane and butanone;
[0042] The poor solvent of the polyphenylene ether is at least one of methanol, ethanol and water;
[0043] The initiator is at least one of dicumyl peroxide, diacyl peroxide initiator and peroxydicarbonate;
[0044] The polymerization inhibitor is at least one of p-benzoquinone, hydroquinone, p-hydroxyanisole, 2-tert-butylhydroquinone and 2,5-di-tert-butylhydroquinone;
[0045] The catalyst is at least one of tetrabutylammonium bromide, tetrabutylammonium chloride, triethylamine, diisopropylethylamine and sodium hydroxide.
[0046] In a second aspect, the present invention further provides a prepreg, which is made from the thermosetting resin composition described in the first aspect and the first to seventh preferred embodiments of the first aspect.
[0047] In a third aspect, the present invention further provides a printed circuit board, comprising a laminate, the laminate comprising an insulating sheet, and a metal foil located on one side or two opposite sides of the insulating sheet, the insulating sheet comprising at least one semi-cured sheet as described in the second aspect.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] The present invention provides a thermosetting resin composition, a prepreg and a printed circuit board manufactured based on the thermosetting resin composition. The thermosetting resin composition of the present invention comprises the following raw materials in parts by weight: a curable polyphenylene ether resin, a multifunctional bismaleimide resin, a benzene ring or heterocyclic vinyl crosslinking agent, a core-shell rubber, a flame retardant, a filler, an accelerator, a vinyl-containing silane coupling agent and a solvent.
[0050] Based on the composite combination of the above materials, the thermosetting resin composition of the present invention has the characteristics of extremely low XY axis expansion coefficient, dielectric constant, low dielectric loss, strong heat resistance, excellent processability, and is very suitable for application in high-frequency and high-speed copper clad laminates, meeting the high standards and strict requirements put forward in the high-frequency and high-speed era. The prepared copper clad laminate is particularly suitable for preparing high-speed circuit substrates. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] The specific embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings, wherein:
[0052] Figure 1 is the structural formula of the phenolic compound for preparing the curable polyphenylene ether resin of the present invention;
[0053] Figure 2 is the structural formula of the end-capping agent for preparing the curable polyphenylene ether resin of the present invention;
[0054] Figure 3 It is the structural formula of the partially curable polyphenylene ether resin prepared by the present invention.
[0055] Figure 4 It is the structural formula of polyphenylene ether resin in the prior art. DETAILED DESCRIPTION
[0056] The following specifically illustrates the implementation mode of the present invention in conjunction with the accompanying drawings. The embodiments are provided for illustrative purposes only and cannot be understood as limiting the present invention. The accompanying drawings are provided for reference and illustration only and do not constitute a limitation on the scope of patent protection of the present invention, because many changes can be made to the present invention without departing from the spirit and scope of the present invention.
[0057] As the basic material for the production of printed circuit boards, copper clad laminates mainly support signal transmission and insulation, and have a significant impact on signal transmission speed and quality. Copper clad laminate substrates are a key component of printed circuit boards, which greatly affects the comprehensive performance and production cost of printed circuit boards. Nowadays, the global communications industry chain has developed to the fifth generation. All kinds of electronic products on the market, such as mobile phones, laptops, tablet computers and other electronic equipment processors and integrated circuit boards are moving towards lighter, more multifunctional, and most importantly, higher speed and higher performance. This requires that the copper clad laminate substrate has other excellent comprehensive properties while having low dielectric constant and dielectric loss.
[0058] Traditional copper clad laminate substrates can no longer meet the requirements of the high-frequency and high-speed era. In order to produce copper clad laminates with better performance, it is particularly important to study the resin materials used to produce copper clad laminate substrates. The resin matrix is a key component material of the copper clad laminate substrate and directly affects the comprehensive performance of a copper clad laminate. Including various epoxy resins, phenolic resins, polyurethanes, polyimides, polyether ketones, etc. Polyphenylene ether itself is a thermoplastic resin and cannot be directly applied to copper clad laminates. Therefore, it is often prepared into modified polyphenylene ether (MPPO) or added to other types of matrix resins to meet the use requirements.
[0059] It has been found that at this stage, the performance of MPPO-based resin products usually has a large XY axis expansion coefficient. To achieve a low expansion coefficient, the content of fillers in the resin products needs to be increased. The current method to achieve low CTE is to add a higher proportion of fillers, which should be added to 60%-75% by mass. Too much filler addition will lead to processing defects, such as poor filling, excessive drilling wear, etc., which cannot be used for high-frequency and high-speed copper clad laminates.
[0060] To this end, the present invention innovatively provides a thermosetting resin based on a curable polyphenylene ether resin, which is used to prepare a prepreg, and is ultimately used in a printed circuit board. And through experiments, it is found that the thermosetting resin composition of the present invention has the characteristics of extremely low XY axis expansion coefficient, dielectric constant, low dielectric loss, strong heat resistance, excellent processability, and is very suitable for application in high-frequency and high-speed copper-clad laminates, meeting the high standards and strict requirements put forward in the high-frequency and high-speed era. The prepared copper-clad laminate is particularly suitable for preparing high-speed circuit substrates.
[0061] First, the present invention innovatively provides a curable polyphenylene ether resin for preparing a thermosetting resin composition, and the structural formula of the curable polyphenylene ether resin is:
[0062]
[0063] In the above structural formula, the structural formula of X is:
[0064]
[0065] In the present invention, R1 and R2 are both curable functional groups containing a biphenyl structure. In a specific implementation, R1 and R2 in the structural formula are independently selected from structural formula I or structural formula II;
[0066] Specifically, structural formula I is:
[0067]
[0068] Specifically, structural formula II is:
[0069]
[0070] Among them, R1 and R2 each contain at least one vinyl group (-CH=CH2). Under this molecular structure, under the action of heat or initiator, free radical addition reaction can occur, and other double bonds in the system will produce intramolecular or intermolecular cross-linking reaction to form a three-dimensional interpenetrating network, providing the material with a higher glass transition temperature.
[0071] In formula I and formula II, R3, R4, R7, and R8 are each independently selected from hydrogen (-H) or methyl (-CH3); R5, R6, R9, and R 10 Each independently selected from hydrogen (-H) or vinyl (-CH=CH2); R5 and R6 are located at the ortho, meta or para position of the benzene ring, and at least one vinyl (-CH=CH2) is contained in R5 and R6; R9 and R 10 Located at the ortho, meta or para position of the benzene ring, and R9 and R 10 Contains at least one vinyl group (-CH=CH2).
[0072] In a specific implementation, the n is selected from an integer of 1 to 50, and the m is selected from an integer of 1 to 50. Preferably, the n is selected from an integer of 1 to 10, and the m is selected from an integer of 1 to 10.
[0073] In the present invention, the number average molecular weight of the curable polyphenylene ether resin is 800 to 1400 g / mol. The more reactive groups there are per unit molecular weight, the higher the degree of crosslinking of the resin when crosslinking occurs.
[0074] After product testing, the curable polyphenylene ether resin used to prepare the thermosetting resin combination of the present invention has the following characteristics:
[0075] (1) Curable polyphenylene ether resin has the advantage of low thermal curing crosslinking temperature, which is 120 to 160°C.
[0076] (2) The curable polyphenylene ether resin has a high solubility in toluene, xylene and butanone solvents at room temperature, and the solubility can reach 55 to 65 wt%.
[0077] (3) The hygroscopicity of the curable polyphenylene ether resin is not more than 0.2%, and when tested at a frequency of 1 GHz, the dielectric constant (Dk) is between 2.44 and 2.48, and the dielectric loss (Df) is between 0.0006 and 0.0008.
[0078] The curable functional groups of the biphenyl structure are contained at both ends of the molecule of the curable polyphenylene ether resin of the present invention, and the resin itself has the advantage of low molecular weight. The crosslinking density of the resin after curing is high, and the cured material has a low XY axis expansion coefficient, extremely low dielectric constant and dielectric loss, and can provide good electrical properties. On the other hand, the biphenyl structure provides excellent toughness and heat resistance for the material; and because the functional group is an unsaturated carbon-carbon double bond, the reaction temperature of the material is low and the crosslinking curing conditions are mild. The curable polyphenylene ether resin of the present invention is very suitable for preparing resin compositions and other downstream products, such as prepregs, copper-clad laminates, etc.
[0079] In a specific implementation, the present invention also provides a method for preparing the above-mentioned curable polyphenylene ether resin, comprising the following steps:
[0080] Step (1): dissolving the single-terminal polyphenylene ether (PPO-OH) in a solvent, stirring to obtain a solution, adding an initiator, a phenolic compound and an inhibitor to the solution for reaction, the reaction temperature is 70 to 80° C., and the reaction time is 5 to 7 hours. After the reaction is completed, precipitation is performed with a poor solvent for the polyphenylene ether, and then filtering and washing to obtain the double-terminal hydroxyl polyphenylene ether (PPO-2OH).
[0081] Among them, the phenolic compound is selected from Figure 1 One of the molecular structural formulas X1, X2, X3 and X4 shown in .
[0082] Step (2): at 60°C, a certain amount of the double-terminated hydroxyl polyphenylene ether (PPO-2OH) obtained in step (1) is dissolved in toluene to obtain a polyphenylene ether solution, and dichloromethane is added to a 10wt% NaOH solution to obtain an alkaline solution. Then, in a nitrogen environment, the alkaline solution is added to the polyphenylene ether solution for reaction for 0.5h, and then tetrabutylammonium bromide is added. Finally, the dichloromethane solution with the end-capping agent is slowly added to the polyphenylene ether solution to react at a certain temperature. The product after the reaction is extracted with ethanol for 4-5 times, and then filtered and vacuum dried for 10h to obtain a vinyl-terminated biphenyl curable polyphenylene ether.
[0083] Wherein, the capping agent is selected from Figure 2The unsaturated olefinic group in the curable polyphenylene ether resin of the present invention is preferably a vinyl group or a propenyl group.
[0084] In a specific implementation, in step (2), when the end-capping agent is a1, a2, a3, or a4, the reaction is carried out for 3 hours at a temperature of 25° C. When the end-capping agent is b1, b2, b3, or b4, the reaction is carried out for 6 hours at a temperature of 60° C.
[0085] Specifically, the single-terminated hydroxyl polyphenylene ether is selected from Hebei Handan Xinbao New Materials Co., Ltd. and its brand is Sinbo RX040@.
[0086] Specifically, the solvent is at least one of benzene, toluene, dichloromethane and butanone. The poor solvent of polyphenylene ether is at least one of methanol, ethanol and water. The initiator is at least one of diisopropylbenzene peroxide, diacyl peroxide initiator and peroxydicarbonate. The inhibitor is at least one of p-benzoquinone, hydroquinone, p-hydroxyanisole, 2-tert-butylhydroquinone and 2,5-di-tert-butylhydroquinone. The catalyst is at least one of tetrabutylammonium bromide, tetrabutylammonium chloride, triethylamine, diisopropylethylamine and sodium hydroxide.
[0087] Combination Figure 2 and Figure 3 The present invention provides multiple specific preparation examples of curable polyphenylene ether resin.
[0088] (1) Preparation Example 1 of Curable Polyphenylene Ether Resin:
[0089] The preparation method of curable polyphenylene ether resin A1 comprises the following steps:
[0090] Step (a): using a single-terminal polyphenylene ether (PPO-OH), adding an initiator, a phenolic compound and an inhibitor to the solution for reaction, the reaction temperature is 70°C, the reaction time is 6 hours, after the reaction is completed, precipitation is carried out with a poor solvent for polyphenylene ether, and then filtering and washing to obtain a double-terminal hydroxyl polyphenylene ether (PPO-2OH).
[0091] Step 1: Material Type Material Name Usage Single-terminated polyphenylene ether PPO-OH 1 part by weight Phenolic compounds Instructions attached Figure 1 X1 in 0.12 parts by weight Inhibitor p-Benzoquinone 0.02 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Initiator Dicumyl peroxide 0.15 parts by weight Solvents Dichloromethane 40 parts by weight
[0092] Step (ii): dissolve a certain amount of double-terminated hydroxyl polyphenylene ether (PPO-2OH) in toluene at 60°C, and after the solution is completed, reduce the temperature to room temperature to obtain a polyphenylene ether solution; add dichloromethane to a 10wt% NaOH solution to obtain an alkaline solution. Then, in a nitrogen environment, add the alkaline solution to the polyphenylene ether solution for reaction for 0.5h, and then add tetrabutylammonium bromide. Finally, slowly add a dichloromethane solution with a certain amount of end-capping agent to the polyphenylene ether solution, react at 25°C for 3h, and extract the product with ethanol for 4-5 times, then filter and vacuum dry for 10h to obtain a vinyl-terminated biphenyl curable polyphenylene ether.
[0093] Step 2: Material Type Material Name Usage Double-terminated hydroxyl polyphenylene ether PPO-2OH prepared in step (a) 1 part by weight Capping agent Instructions attached Figure 2 a1 in 0.45 parts by weight Basic catalyst Sodium hydroxide 0.08 parts by weight Phase transfer catalyst Tetrabutylammonium bromide 0.05 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Solvents Dichloromethane / Toluene 5 parts by weight
[0094] The number average molecular weight Mn of the curable polyphenylene ether resin A1 prepared in this Example 1 is 1253, the curing and crosslinking temperature is 147.5°C, the solubility in butanone is 65wt%, the hygroscopicity is 0.09%, and the test at a frequency of 1 GHz: Dk is 2.48, and Df is 0.0007.
[0095] (2) Preparation Example 2 of Curable Polyphenylene Ether Resin:
[0096] The preparation method of curable polyphenylene ether resin A2 comprises the following steps:
[0097] Step (a): using a single-terminal polyphenylene ether (PPO-OH), adding an initiator, a phenolic compound and an inhibitor to the solution for reaction, the reaction temperature is 70°C, the reaction time is 6 hours, after the reaction is completed, precipitation is carried out with a poor solvent for polyphenylene ether, and then filtering and washing to obtain a double-terminal hydroxyl polyphenylene ether (PPO-2OH).
[0098] Step 1: Material Type Material Name Usage Single-terminated polyphenylene ether PPO-OH 1 part by weight Phenolic compounds Instructions attached Figure 1 X2 0.12 parts by weight Inhibitor p-Benzoquinone 0.02 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Initiator Dicumyl peroxide 0.15 parts by weight Solvents Dichloromethane 40 parts by weight
[0099] Step (ii): dissolve a certain amount of double-terminated hydroxyl polyphenylene ether (PPO-2OH) in toluene at 60°C, and after the solution is completed, reduce the temperature to room temperature to obtain a polyphenylene ether solution; add dichloromethane to a 10wt% NaOH solution to obtain an alkaline solution. Then, in a nitrogen environment, add the alkaline solution to the polyphenylene ether solution for reaction for 0.5h, and then add tetrabutylammonium bromide. Finally, slowly add a dichloromethane solution with a certain amount of end-capping agent to the polyphenylene ether solution, react at 25°C for 3h, and extract the product with ethanol for 4-5 times, then filter and vacuum dry for 10h to obtain a vinyl-terminated biphenyl curable polyphenylene ether.
[0100] Step 2: Material Type Material Name Usage Double-terminated hydroxyl polyphenylene ether PPO-2OH prepared in step (a) 1 part by weight Capping agent Instructions attached Figure 2 a1 in 0.45 parts by weight Basic catalyst Sodium hydroxide 0.08 parts by weight Phase transfer catalyst Tetrabutylammonium bromide 0.05 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Solvents Dichloromethane / Toluene 5 parts by weight
[0101] The number average molecular weight Mn of the curable polyphenylene ether resin A2 prepared in this Example 2 is 1315, the curing and crosslinking temperature is 150.5°C, the solubility in butanone is 60wt%, the hygroscopicity is 0.07%, and the test at a frequency of 1 GHz: Dk is 2.46, and Df is 0.0006.
[0102] (3) Preparation Example 3 of Curable Polyphenylene Ether Resin:
[0103] The preparation method of curable polyphenylene ether resin A3 comprises the following steps:
[0104] Step (a): using a single-terminal polyphenylene ether (PPO-OH), adding an initiator, a phenolic compound and an inhibitor to the solution for reaction, the reaction temperature is 70°C, the reaction time is 6 hours, after the reaction is completed, precipitation is carried out with a poor solvent for polyphenylene ether, and then filtering and washing to obtain a double-terminal hydroxyl polyphenylene ether (PPO-2OH).
[0105] Step 1: Material Type Material Name Usage Single-terminated polyphenylene ether PPO-OH 1 part by weight Phenolic compounds Instructions attached Figure 1 X3 in 0.12 parts by weight Inhibitor p-Benzoquinone 0.02 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Initiator Dicumyl peroxide 0.15 parts by weight Solvents Dichloromethane 40 parts by weight
[0106] Step (ii): dissolve a certain amount of double-terminated hydroxyl polyphenylene ether (PPO-2OH) in toluene at 60°C, and after the solution is completed, reduce the temperature to room temperature to obtain a polyphenylene ether solution; add dichloromethane to a 10wt% NaOH solution to obtain an alkaline solution. Then, in a nitrogen environment, add the alkaline solution to the polyphenylene ether solution for reaction for 0.5h, and then add tetrabutylammonium bromide. Finally, slowly add a dichloromethane solution with a certain amount of end-capping agent to the polyphenylene ether solution, react at 25°C for 3h, and extract the product with ethanol for 4-5 times, then filter and vacuum dry for 10h to obtain a vinyl-terminated biphenyl curable polyphenylene ether.
[0107] Step 2: Material Type Material Name Usage Double-terminated hydroxyl polyphenylene ether PPO-2OH prepared in step (a) 1 part by weight Capping agent Instructions attached Figure 2 a1 in 0.45 parts by weight Basic catalyst Sodium hydroxide 0.08 parts by weight Phase transfer catalyst Tetrabutylammonium bromide 0.05 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Solvents Dichloromethane / Toluene 5 parts by weight
[0108] The number average molecular weight Mn of the curable polyphenylene ether resin A3 prepared in this Example 3 is 1108, the heat curing crosslinking temperature is 146.8°C, the solubility in butanone is 65wt%, the hygroscopicity is 0.10%, and the test at a frequency of 1 GHz: Dk is 2.47, and Df is 0.0007.
[0109] (4) Preparation Example 4 of Curable Polyphenylene Ether Resin:
[0110] The preparation method of curable polyphenylene ether resin A4 comprises the following steps:
[0111] Step (a): using a single-terminal polyphenylene ether (PPO-OH), adding an initiator, a phenolic compound and an inhibitor to the solution for reaction, the reaction temperature is 70°C, the reaction time is 6 hours, after the reaction is completed, precipitation is carried out with a poor solvent for polyphenylene ether, and then filtering and washing to obtain a double-terminal hydroxyl polyphenylene ether (PPO-2OH).
[0112] Step 1: Material Type Material Name Usage Single-terminated polyphenylene ether PPO-OH 1 part by weight Phenolic compounds Instructions attached Figure 1 X4 in 0.1 parts by weight Inhibitor p-Benzoquinone 0.02 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Initiator Dicumyl peroxide 0.15 parts by weight Solvents Dichloromethane 40 parts by weight
[0113] Step (ii): dissolve a certain amount of double-terminated hydroxyl polyphenylene ether (PPO-2OH) in toluene at 60°C, and after the solution is completed, reduce the temperature to room temperature to obtain a polyphenylene ether solution; add dichloromethane to a 10wt% NaOH solution to obtain an alkaline solution. Then, in a nitrogen environment, add the alkaline solution to the polyphenylene ether solution for reaction for 0.5h, and then add tetrabutylammonium bromide. Finally, slowly add a dichloromethane solution with a certain amount of end-capping agent to the polyphenylene ether solution, react at 25°C for 3h, and extract the product with ethanol for 4-5 times, then filter and vacuum dry for 10h to obtain a vinyl-terminated biphenyl curable polyphenylene ether.
[0114] Step 2: Material Type Material Name Usage Double-terminated hydroxyl polyphenylene ether PPO-2OH prepared in step (a) 1 part by weight Capping agent Instructions attached Figure 2 a1 in 0.45 parts by weight Basic catalyst Sodium hydroxide 0.08 parts by weight Phase transfer catalyst Tetrabutylammonium bromide 0.05 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Solvents Dichloromethane 5 parts by weight
[0115] The number average molecular weight Mn of the curable polyphenylene ether resin A4 prepared in this Example 4 is 1158, the thermal curing crosslinking temperature is 149.2°C, the solubility in butanone is 65wt%, the hygroscopicity is 0.08%, and the test at a frequency of 1 GHz: Dk is 2.46, and Df is 0.0006.
[0116] (5) Preparation Example 5 of Curable Polyphenylene Ether Resin:
[0117] The preparation method of curable polyphenylene ether resin A5 comprises the following steps:
[0118] Step (a): using a single-terminal polyphenylene ether (PPO-OH), adding an initiator, a phenolic compound and an inhibitor to the solution for reaction, the reaction temperature is 70°C, the reaction time is 6 hours, after the reaction is completed, precipitation is carried out with a poor solvent for polyphenylene ether, and then filtering and washing to obtain a double-terminal hydroxyl polyphenylene ether (PPO-2OH).
[0119]
[0120]
[0121] Step (ii): dissolve a certain amount of double-terminated hydroxyl polyphenylene ether (PPO-2OH) in toluene at 60°C, and after the solution is completed, reduce the temperature to room temperature to obtain a polyphenylene ether solution; add dichloromethane to a 10wt% NaOH solution to obtain an alkaline solution. Then, in a nitrogen environment, add the alkaline solution to the polyphenylene ether solution for reaction for 0.5h, and then add tetrabutylammonium bromide. Finally, slowly add a dichloromethane solution with a certain amount of end-capping agent to the polyphenylene ether solution, react at 25°C for 3h, and extract the product with ethanol for 4-5 times, then filter and vacuum dry for 10h to obtain a vinyl-terminated biphenyl curable polyphenylene ether.
[0122] Step 2: Material Type Material Name Usage Double-terminated hydroxyl polyphenylene ether PPO-2OH prepared in step (a) 1 part by weight Capping agent Instructions attached Figure 2 a2 0.40 parts by weight Basic catalyst Sodium hydroxide 0.08 parts by weight Phase transfer catalyst Tetrabutylammonium bromide 0.05 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Solvents Dichloromethane 5 parts by weight
[0123] The curable polyphenylene ether resin A5 prepared in this Example 5 has a number average molecular weight Mn of 1400, a thermal curing crosslinking temperature of 139.3°C, a solubility in butanone of 60wt%, a hygroscopicity of 0.08%, and a test at a frequency of 1 GHz: Dk is 2.48, and Df is 0.0007.
[0124] (6) Preparation Example 6 of Curable Polyphenylene Ether Resin:
[0125] The preparation method of curable polyphenylene ether resin A6 comprises the following steps:
[0126] Step (a): using a single-terminal polyphenylene ether (PPO-OH), adding an initiator, a phenolic compound and an inhibitor to the solution for reaction, the reaction temperature is 70°C, the reaction time is 6 hours, after the reaction is completed, precipitation is carried out with a poor solvent for polyphenylene ether, and then filtering and washing to obtain a double-terminal hydroxyl polyphenylene ether (PPO-2OH).
[0127]
[0128]
[0129] Step (ii): dissolve a certain amount of double-terminated hydroxyl polyphenylene ether (PPO-2OH) in toluene at 60°C, and after the solution is completed, reduce the temperature to room temperature to obtain a polyphenylene ether solution; add dichloromethane to a 10wt% NaOH solution to obtain an alkaline solution. Then, in a nitrogen environment, add the alkaline solution to the polyphenylene ether solution for reaction for 0.5h, and then add tetrabutylammonium bromide. Finally, slowly add a dichloromethane solution with a certain amount of end-capping agent to the polyphenylene ether solution, react at 25°C for 3h, and extract the product with ethanol for 4-5 times, then filter and vacuum dry for 10h to obtain a vinyl-terminated biphenyl curable polyphenylene ether.
[0130] Step 2: Material Type Material Name Usage Double-terminated hydroxyl polyphenylene ether PPO-2OH prepared in step (a) 1 part by weight Capping agent Instructions attached Figure 2 a3 in 0.45 parts by weight Basic catalyst Sodium hydroxide 0.08 parts by weight Phase transfer catalyst Tetrabutylammonium bromide 0.05 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Solvents Dichloromethane 5 parts by weight
[0131] The number average molecular weight Mn of the curable polyphenylene ether resin A6 prepared in this Example 6 is 1266, the thermal curing crosslinking temperature is 135.2°C, the solubility in butanone is 60wt%, the hygroscopicity is 0.09%, and the test at a frequency of 1 GHz: Dk is 2.49, and Df is 0.0007.
[0132] (7) Preparation Example 7 of Curable Polyphenylene Ether Resin:
[0133] The preparation method of curable polyphenylene ether resin A7 comprises the following steps:
[0134] Step (a): using a single-terminal polyphenylene ether (PPO-OH), adding an initiator, a phenolic compound and an inhibitor to the solution for reaction, the reaction temperature is 70°C, the reaction time is 6 hours, after the reaction is completed, precipitation is carried out with a poor solvent for polyphenylene ether, and then filtering and washing to obtain a double-terminal hydroxyl polyphenylene ether (PPO-2OH).
[0135]
[0136]
[0137] Step (ii): dissolve a certain amount of double-terminated hydroxyl polyphenylene ether (PPO-2OH) in toluene at 60°C, and after the solution is completed, reduce the temperature to room temperature to obtain a polyphenylene ether solution; add dichloromethane to a 10wt% NaOH solution to obtain an alkaline solution. Then, in a nitrogen environment, add the alkaline solution to the polyphenylene ether solution for reaction for 0.5h, and then add tetrabutylammonium bromide. Finally, slowly add a dichloromethane solution with a certain amount of end-capping agent to the polyphenylene ether solution, react at 25°C for 3h, and extract the product with ethanol for 4-5 times, then filter and vacuum dry for 10h to obtain a vinyl-terminated biphenyl curable polyphenylene ether.
[0138] Step 2: Material Type Material Name Usage Double-terminated hydroxyl polyphenylene ether PPO-2OH prepared in step (a) 1 part by weight Capping agent Instructions attached Figure 2 a4 in 0.70 parts by weight Basic catalyst Sodium hydroxide 0.08 parts by weight Phase transfer catalyst Tetrabutylammonium bromide 0.05 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Solvents Dichloromethane 5 parts by weight
[0139] The curable polyphenylene ether resin A7 prepared in this Example 7 has a number average molecular weight Mn of 800, a thermal curing crosslinking temperature of 120.0°C, a solubility in butanone of 65wt%, a hygroscopicity of 0.13%, and a test at a frequency of 1 GHz: Dk is 2.48, and Df is 0.0007.
[0140] (8) Preparation Example 8 of Curable Polyphenylene Ether Resin:
[0141] The preparation method of curable polyphenylene ether resin A8 comprises the following steps:
[0142] Step (a): using a single-terminal polyphenylene ether (PPO-OH), adding an initiator, a phenolic compound and an inhibitor to the solution for reaction, the reaction temperature is 80°C, the reaction time is 6 hours, after the reaction is completed, precipitation is carried out with a poor solvent for polyphenylene ether, and then filtering and washing to obtain a double-terminal hydroxyl polyphenylene ether (PPO-2OH).
[0143]
[0144]
[0145] Step (ii): dissolve a certain amount of double-terminated hydroxyl polyphenylene ether (PPO-2OH) in toluene at 60°C, and after the solution is completed, reduce the temperature to room temperature to obtain a polyphenylene ether solution; add dichloromethane to a 10wt% NaOH solution to obtain an alkaline solution. Then, in a nitrogen environment, add the alkaline solution to the polyphenylene ether solution for reaction for 0.5h, and then add tetrabutylammonium bromide. Finally, slowly add a dichloromethane solution with a certain amount of end-capping agent to the polyphenylene ether solution, react at 60°C for 6h, and extract the product with ethanol for 4-5 times, then filter and vacuum dry for 10h to obtain a vinyl-terminated biphenyl curable polyphenylene ether.
[0146] Step 2: Material Type Material Name Usage Double-terminated hydroxyl polyphenylene ether PPO-2OH prepared in step (a) 1 part by weight Capping agent Instructions attached Figure 2 b1 0.5 parts by weight Basic catalyst Sodium hydroxide 0.08 parts by weight Phase transfer catalyst Tetrabutylammonium bromide 0.05 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Solvents Dichloromethane 5 parts by weight
[0147] The curable polyphenylene ether resin A8 prepared in this Example 8 has a number average molecular weight Mn of 1224, a thermal curing crosslinking temperature of 129.3°C, a solubility in butanone of 60wt%, a hygroscopicity of 0.011%, and a test at a frequency of 1 GHz: Dk is 2.48, and Df is 0.0008.
[0148] (9) Preparation Example 9 of Curable Polyphenylene Ether Resin:
[0149] The preparation method of curable polyphenylene ether resin A9 comprises the following steps:
[0150] Step (a): using a single-terminal polyphenylene ether (PPO-OH), adding an initiator, a phenolic compound and an inhibitor to the solution for reaction, the reaction temperature is 75°C, the reaction time is 6 hours, after the reaction is completed, precipitation is carried out with a poor solvent for polyphenylene ether, and then filtering and washing to obtain a double-terminal hydroxyl polyphenylene ether (PPO-2OH).
[0151]
[0152]
[0153] Step (ii): dissolve a certain amount of double-terminated hydroxyl polyphenylene ether (PPO-2OH) in toluene at 60°C, and after the solution is completed, reduce the temperature to room temperature to obtain a polyphenylene ether solution; add dichloromethane to a 10wt% NaOH solution to obtain an alkaline solution. Then, in a nitrogen environment, add the alkaline solution to the polyphenylene ether solution for reaction for 0.5h, and then add tetrabutylammonium bromide. Finally, slowly add a dichloromethane solution with a certain amount of end-capping agent to the polyphenylene ether solution, react at 60°C for 6h, and extract the product with ethanol for 4-5 times, then filter and vacuum dry for 10h to obtain a vinyl-terminated biphenyl curable polyphenylene ether.
[0154]
[0155] The curable polyphenylene ether resin A9 prepared in this Example 9 has a number average molecular weight Mn of 1212, a thermal curing crosslinking temperature of 149.8°C, a solubility in butanone of 65wt%, a hygroscopicity of 0.09%, and a test at a frequency of 1 GHz: Dk is 2.46, and Df is 0.0007.
[0156] (10) Preparation Example 10 of Curable Polyphenylene Ether Resin:
[0157] The preparation method of curable polyphenylene ether resin A10 comprises the following steps:
[0158] Step (a): using a single-terminal polyphenylene ether (PPO-OH), adding an initiator, a phenolic compound and an inhibitor to the solution for reaction, the reaction temperature is 70°C, the reaction time is 5 hours, after the reaction is completed, precipitation is carried out with a poor solvent for polyphenylene ether, and then filtering and washing to obtain a double-terminal hydroxyl polyphenylene ether (PPO-2OH).
[0159]
[0160]
[0161] Step (ii): dissolve a certain amount of double-terminated hydroxyl polyphenylene ether (PPO-2OH) in toluene at 60°C, and after the solution is completed, reduce the temperature to room temperature to obtain a polyphenylene ether solution; add dichloromethane to a 10wt% NaOH solution to obtain an alkaline solution. Then, in a nitrogen environment, add the alkaline solution to the polyphenylene ether solution for reaction for 0.5h, and then add tetrabutylammonium bromide. Finally, slowly add a dichloromethane solution with a certain amount of end-capping agent to the polyphenylene ether solution, react at 60°C for 6h, and extract the product with ethanol for 4-5 times, then filter and vacuum dry for 10h to obtain a vinyl-terminated biphenyl curable polyphenylene ether.
[0162] Step 2: Material Type Material Name Usage Double-terminated hydroxyl polyphenylene ether PPO-2OH prepared in step (a) 1 part by weight Capping agent Instructions attached Figure 2 b3 in 0.50 parts by weight Basic catalyst Sodium hydroxide 0.08 parts by weight Phase transfer catalyst Tetrabutylammonium bromide 0.05 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Solvents Dichloromethane 5 parts by weight
[0163] The curable polyphenylene ether resin A10 prepared in this Example 10 has a number average molecular weight Mn of 1184, a thermal curing crosslinking temperature of 133.5°C, a solubility in butanone of 60wt%, a hygroscopicity of 0.07%, and a test at a frequency of 1 GHz: Dk is 2.48, and Df is 0.0007.
[0164] (11) Preparation Example 11 of Curable Polyphenylene Ether Resin:
[0165] The preparation method of curable polyphenylene ether resin A11 comprises the following steps:
[0166] Step (a): using a single-terminal polyphenylene ether (PPO-OH), adding an initiator, a phenolic compound and an inhibitor to the solution for reaction, the reaction temperature is 70°C, the reaction time is 7h, after the reaction is completed, precipitation is carried out with a poor solvent for polyphenylene ether, and then filtering and washing to obtain a double-terminal hydroxyl polyphenylene ether (PPO-2OH).
[0167] Step 1: Material Type Material Name Usage Single-terminated polyphenylene ether PPO-OH 1 part by weight Phenolic compounds Instructions attached Figure 1 X4 in 0.12 parts by weight Inhibitor p-Benzoquinone 0.02 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Initiator Dicumyl peroxide 0.15 parts by weight Solvents Dichloromethane 40 parts by weight
[0168] Step (ii): dissolve a certain amount of double-terminated hydroxyl polyphenylene ether (PPO-2OH) in toluene at 60°C, and after the solution is completed, reduce the temperature to room temperature to obtain a polyphenylene ether solution; add dichloromethane to a 10wt% NaOH solution to obtain an alkaline solution. Then, in a nitrogen environment, add the alkaline solution to the polyphenylene ether solution for reaction for 0.5h, and then add tetrabutylammonium bromide. Finally, slowly add a dichloromethane solution with a certain amount of end-capping agent to the polyphenylene ether solution, react at 60°C for 6h, and extract the product with ethanol for 4-5 times, then filter and vacuum dry for 10h to obtain a vinyl-terminated biphenyl curable polyphenylene ether.
[0169] Step 2: Material Type Material Name Usage Double-terminated hydroxyl polyphenylene ether PPO-2OH prepared in step (a) 1 part by weight Capping agent Instructions attached Figure 2 b4 0.50 parts by weight Basic catalyst Sodium hydroxide 0.08 parts by weight Phase transfer catalyst Tetrabutylammonium bromide 0.05 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Solvents Dichloromethane 5 parts by weight
[0170] The curable polyphenylene ether resin A11 prepared in this Example 11 has a number average molecular weight Mn of 1150, a thermal curing crosslinking temperature of 148.6°C, a solubility in butanone of 65wt%, a hygroscopicity of 0.08%, and a test at a frequency of 1 GHz: Dk is 2.47, and Df is 0.0006.
[0171] Furthermore, the present invention also provides a comparative example of a curable polyphenylene ether resin:
[0172] Comparative Example 1 of Curable Polyphenylene Ether Resin:
[0173] The preparation method of curable polyphenylene ether resin A12 comprises the following steps:
[0174] Step (a): using a single-terminal polyphenylene ether (PPO-OH), adding an initiator, a phenolic compound and an inhibitor to the solution for reaction, the reaction temperature is 70°C, the reaction time is 6 hours, after the reaction is completed, precipitation is carried out with a poor solvent for polyphenylene ether, and then filtering and washing to obtain a double-terminal hydroxyl polyphenylene ether (PPO-2OH).
[0175] Step 1: Material Type Material Name Usage Single-terminated polyphenylene ether PPO-OH 1 part by weight Phenolic compounds Instructions attached Figure 1 X4 in 0.10 parts by weight Inhibitor p-Benzoquinone 0.01 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Initiator Dicumyl peroxide 0.12 parts by weight Solvents Dichloromethane 40 parts by weight
[0176] Step (ii): dissolve a certain amount of double-terminated hydroxyl polyphenylene ether (PPO-2OH) in toluene at 60°C, and after the solution is completed, reduce the temperature to room temperature to obtain a polyphenylene ether solution; add dichloromethane to a 10wt% NaOH solution to obtain an alkaline solution. Then, in a nitrogen environment, add the alkaline solution to the polyphenylene ether solution for reaction for 0.5h, and then add tetrabutylammonium bromide. Finally, slowly add a dichloromethane solution with a certain amount of end-capping agent to the polyphenylene ether solution, react at 60°C for 6h, and extract the product with ethanol for 4-5 times, then filter and vacuum dry for 10h to obtain a vinyl-terminated biphenyl curable polyphenylene ether.
[0177] Step 2: Material Type Material Name Usage Double-terminated hydroxyl polyphenylene ether PPO-2OH prepared in step (a) 1 part by weight Capping agent Instructions attached Figure 2 b2 0.50 parts by weight Basic catalyst Sodium hydroxide 0.04 parts by weight Phase transfer catalyst Tetrabutylammonium bromide 0.05 parts by weight Polyphenylene ether poor solvent Ethanol 60 parts by weight Solvents Dichloromethane 15 parts by weight
[0178] The number average molecular weight Mn of the curable polyphenylene ether resin A12 prepared in Comparative Example 1 is 2185, the curing and crosslinking temperature is 167.3°C, the solubility in butanone is 60wt%, the hygroscopicity is 0.07%, and the test at a frequency of 1 GHz: Dk is 2.44, and Df is 0.0006.
[0179] Based on the above examples, it can be seen that in the present invention, bihydroxyphenols containing biphenyl structure, norbornene, and benzonorbornene structure are used to react with single-terminated hydroxyl polyphenylene ether, and a redistribution reaction is performed to adjust the molecular weight of the polyphenylene ether, synthesize bihydroxyl polyphenylene ether containing norbornene and benzonorbornene structure and having a small molecular weight, and then react with a vinyl end-capping agent containing biphenyl structure to perform end-capping to complete the modification of the molecular chain end group. Finally, a curable polyphenylene ether resin with a number average molecular weight of 800 to 1400 g / mol is obtained.
[0180] According to the use requirements, the types and quantities of the middle structure and the end groups can be molecularly designed. Different dihydroxyphenols and end capping agents are used in the two-step reaction to achieve the purpose of designing and adjusting the types and quantities of carbon-carbon double bond groups in the molecular chain of the curable polyphenylene ether resin. The middle structure and end group structure of the cross-linkable curable polyphenylene ether can effectively improve the toughness of the polyphenylene ether, so that the cured material has good processability. The number average molecular weight of 800 to 1400 g / mol can significantly increase the cross-linking density of the polyphenylene ether and effectively reduce the thermal expansion coefficient of the polyphenylene ether, so that the initial decomposition temperature of the cured material is 393 to 417°C and the glass transition temperature is 200.5 to 214.3°C.
[0181] In a preferred embodiment, as the end groups of the chain structure of the curable polyphenylene ether, R1 and R2 each contain at least one vinyl group. Under this molecular structure, under the action of heat or an initiator, a free radical addition reaction can occur, and an intramolecular or intermolecular cross-linking reaction with other double bonds in the system can be generated to form a three-dimensional interpenetrating network, providing the material with a higher glass transition temperature.
[0182] The applicant has found that if the molecular weight is too small and the content of curable groups per unit molecular weight is too large, the cured product after cross-linking of the resin will be more brittle. However, if the molecular weight is too large, the XY-axis thermal expansion coefficient of the cross-linked material will increase, which will lead to a larger expansion coefficient of the polyphenylene ether system and make it difficult to meet the PCB terminal's demand for a lower expansion coefficient of the material.
[0183] To this end, the present invention adjusts the molecular weight of the curable polyphenylene ether through a specific design, and finally obtains a curable polyphenylene ether resin with a number average molecular weight of 800 to 1400 g / mol, which can effectively solve the problem that the existing MPPO polyphenylene ether resin composition cannot achieve low XY axis CTE and has good PCB processing performance.
[0184] Specifically, R1 and R2 in the structural formula of the curable polyphenylene ether resin of the present invention are independently selected from structural formula I or structural formula II;
[0185] Structural formula I is:
[0186]
[0187] Structural formula II is:
[0188]
[0189] In the above structural formula I and structural formula II, R3, R4, R7, and R8 are each independently selected from hydrogen or methyl; R5, R6, R9, and R 10 Each independently selected from hydrogen or vinyl; R5 and R6 are located at the ortho, meta or para position of the benzene ring, and at least one vinyl group is contained in R5 and R6; R9 and R 10 Located at the ortho, meta or para position of the benzene ring, and R9 and R 10 Contains at least one vinyl group.
[0190] The curable polyphenylene ether resin contained in the resin composition has curable functional groups with biphenyl structures at both ends of the molecule, and the number average molecular weight is 800-1400 g / mol. Under this design, the content of curable functional groups per unit molecular weight is high, and the curing crosslinking density is high; at the same time, the biphenyl structure provides the material with excellent toughness and heat resistance. Since the functional group is an unsaturated carbon-carbon double bond, the reaction temperature is low and the crosslinking curing conditions are mild.
[0191] Specifically, the structural formula of X in the structural formula of the curable polyphenylene ether resin is:
[0192]
[0193] Wherein, the n is selected from an integer of 1 to 50, and the m is selected from an integer of 1 to 50.
[0194] like Figure 4 As shown in the figure, the structures of two PPO resins commonly used in copper clad laminates are: Figure 4 (a) is a double-terminated hydroxyl PPO resin; Figure 4 (b) is a double-terminal acrylate-based PPO resin. Commonly used PPO resins are acrylate-terminated PPO. In contrast, the polyphenylene ether resin provided by the present invention has a biphenyl type or norbornene structure in the middle of the molecular chain, which forms a large delocalized π bond with the other parts of the polyphenylene ether structure, so that the polyphenylene ether molecule segments are in the same plane area, ensuring that the polyphenylene ether has extremely low polarity. At the same time, the end groups at both ends of the molecular chain are olefinic groups containing biphenyl structures, and the interpenetrating network structure formed after cross-linking is non-polar, the resin is not hygroscopic, and the cured material has extremely low dielectric constant and dielectric loss, which can provide good electrical properties. Further, the present invention, through the introduction of biphenyl and dicyclopentadiene structures, makes the cured material have good toughness, improves the heat resistance of the material and the processability of the PCB segment.
[0195] Product experiments have found that the resin composition and prepreg prepared by using the curable polyphenylene ether resin of the present invention have the characteristics of extremely low expansion coefficient, dielectric constant, low dielectric loss, and strong heat resistance, and are very suitable for application in high-frequency and high-speed copper clad laminates, meeting the high standards and strict requirements put forward in the high-frequency and high-speed era. The prepared copper clad laminate is particularly suitable for preparing high-speed circuit substrates.
[0196] Furthermore, the applicant has found that with the development of miniaturization, multifunctionality and high performance of electronic and information communication equipment, the chip integration is getting higher and higher, and the packaging technology is also improving day by day, which puts higher requirements on the performance of the substrate material carrying the semiconductor components, especially the coefficient of thermal expansion (CTE). If the CTE difference between the semiconductor component and the substrate is too large, the substrate will easily warp due to the CTE difference under heating conditions, resulting in serious problems such as poor connection between the semiconductor component and the substrate, and between the substrate and the PCB. However, the current MPPO resin material is difficult to meet the application needs of lower X / Y axis thermal expansion coefficient at a low filling ratio.
[0197] To this end, the present invention provides a thermosetting resin composition, comprising a curable polyphenylene ether prepared by the present invention, a multifunctional bismaleimide resin, a benzene ring or heterocyclic vinyl crosslinking agent, a core-shell rubber, a flame retardant, a filler, an accelerator, a vinyl-containing silane coupling agent and a solvent. The thermosetting resin composition can effectively solve the problem that the existing MPPO polyphenylene ether resin composition cannot achieve low X / Y axis CTE and low dielectric properties at a low filling ratio, and has good PCB processing performance.
[0198] Specifically, the thermosetting resin composition of the present invention comprises the following raw materials in parts by weight:
[0199] 20-50 parts of curable polyphenylene ether resin;
[0200] 10-30 parts of multifunctional bismaleimide resin;
[0201] Containing 30-70 parts of benzene ring or heterocyclic vinyl crosslinking agent;
[0202] Core-shell rubber 0-6 parts;
[0203] 1 to 15 parts of flame retardant;
[0204] 100-150 parts of filler;
[0205] Accelerator 0.1-1 part;
[0206] 0.1 to 1 part of vinyl-containing silane coupling agent;
[0207] 50 to 100 parts of solvent.
[0208] In a specific implementation, in order to optimize the X / Y axis CTE performance of the thermosetting resin composition, the present invention creatively makes major improvements in the following aspects:
[0209] (1) The number average molecular weight of the curable polyphenylene ether resin of the present invention is 800 to 1400 g / mol. Under this unit molecular weight, there are many reactive groups, the degree of crosslinking is high during crosslinking, and the glass transition temperature of the cured material is high, so that the expansion coefficient of the polyphenylene ether system is small, meeting the requirements of the PCB terminal for materials with lower expansion coefficients. If the molecular weight is too large, the X / Y axis thermal expansion coefficient of the material after crosslinking becomes large, and the problem of the large expansion coefficient of the polyphenylene ether system cannot be solved.
[0210] Specifically, the curable polyphenylene ether resin of the present invention is characterized in that the middle of the molecular chain contains biphenyl structure, norbornene, benzonorbornene structure and unsaturated carbon-carbon double bonds of biphenyl structure at both ends. Under the action of heat or initiator in processing applications, free radical addition reaction can be carried out to form a three-dimensional network structure. The biphenyl and norbornene structures improve the toughness of the cured product in the cured three-dimensional network structure, and the benzene heterocyclic structure reduces the material expansion coefficient. And according to needs, the double bond content at both ends of the curable polyphenylene ether resin can be adjusted by the double bond content in the end-capping agent, thereby achieving functions such as controllable crosslinking degree and designable material properties.
[0211] (2) Bismaleimide (BMI) resin is a bifunctional polymer with maleimide group as the active end group. It is a type of resin system separated from the polyimide resin system.
[0212] The multifunctional bismaleimide resin of the present invention includes a bismaleimide monomer having at least three functional groups, which is used to promote a curing reaction. The unsaturated double bond groups in the resin structure can react with the unsaturated double bond groups in the curable polyphenylene ether, thereby promoting crosslinking and curing, forming more crosslinking points, and increasing the crosslinking density, thereby reducing the thermal expansion coefficient of the material.
[0213] (3) The present invention uses a crosslinking agent containing a benzene ring or a heterocyclic vinyl. Since the benzene ring or the heterocyclic ring is created in the crosslinking agent, the mobility of the chain segments between the crosslinking points is reduced. When the cured product is subjected to thermal force, the benzene heterocyclic structure between the crosslinking points can increase the resistance to molecular movement and increase the rigidity of the cured product. Therefore, the thermal expansion coefficient of the cured product can be reduced to a certain extent, so that the overall thermal expansion coefficient of the polyphenylene ether cured product can be lowered.
[0214] In a specific implementation, the benzene ring or heterocyclic vinyl crosslinking agent is divinylbenzene, 4,4'-divinylbiphenyl, 4,4'-diallyl-1,1'-biphenyl, vinyl norbornene, 2,2-diallyl-4,4'-biphenol, and at least two of an unsaturated styrene-butadiene copolymer having a base number average molecular weight of 800 to 2000 g / mol, triallyl isocyanate and vinyl phosphazene.
[0215] The cross-linking agent defined above in the present invention contains multiple reactive non-polar double bonds, so that when the cross-linking agent participates in a free radical polymerization reaction to form a three-dimensional network structure, the dielectric constant and dielectric loss of the material can be kept unchanged. The presence of multiple benzene rings and heterocyclic rings in the molecule can further reduce the thermal expansion coefficient of the cured product after participating in cross-linking curing.
[0216] (4) Fillers mainly play a reinforcing role. The shape, size, surface treatment method and amount of fillers added will have a great impact on the performance of the material. The present invention prefers spherical fillers. The use of fillers in copper-clad laminates can significantly reduce the thermal expansion coefficient of the board material and improve the reliability of component welding on printed circuit boards. If the expansion coefficient of the material is large, the expansion degree of the welded components and the board itself is inconsistent, which will cause the component pins to crack and cause component failure.
[0217] In a preferred implementation, the filler includes nano-spherical silicon and micro-spherical silicon. The applicant has found that the larger the average particle size of the filler, the more defects are generated inside the material, and the smaller the average particle size of the filler, the greater the surface energy, and the easier it is to agglomerate, resulting in uneven distribution of the filler inside the material. At this time, it is required to compound the filler and perform surface treatment on it to reduce the surface energy so that it is evenly dispersed in the matrix resin. The present invention uses nano-spherical silicon and micro-spherical silicon in combination to improve the PCB processability and reliability of the material.
[0218] In a specific implementation, the filler is spherical silicon dioxide, preferably a compound of spherical silicon dioxide with a particle size D50 of 500 nanometers and a particle size D50 of 5 micrometers. In a specific implementation, the nano-spherical silicon dioxide accounts for 5% to 30% of the total weight of the filler, and the micro-spherical silicon dioxide accounts for 70% to 95% of the total weight of the filler. Through this design, the packing density of the filler balls can be increased, and the PCB processability and reliability of the material can be improved.
[0219] The present invention creatively realizes the advantages of low X / Y-axis thermal expansion coefficient and low dielectric performance of low dielectric constant materials through the synergistic combination of the above multiple technical means, and has good PCB processing performance.
[0220] In a preferred embodiment, the core-shell rubber is nano core-shell rubber CSR. By adding CSR, when the toughness of the material is insufficient, the damage of the material during mechanical drilling can be reduced to a certain extent, thereby improving its processability.
[0221] In a preferred implementation, the flame retardant is a halogen-free phosphorus-containing flame retardant. In a specific implementation, the flame retardant is selected from one of vinyl phosphazene, bis(4-carboxyphenyl)phenylphosphine oxide, bis(3,5-dimethylphenyl)phosphine oxide, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-HQ), 10-(2,5-dihydroxy-4-phenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, triphenylphosphine oxide and p-xylylbisdiphenylphosphine oxide. For example, the vinyl phosphazene can be tri(2-propenyl)phenoxytriphenoxycyclotriphosphazene.
[0222] In this field, the limiting oxygen index of organic polymer materials is lower than 28, which is a flammable product. For copper clad laminate materials, flame retardancy is a performance evaluation index, and the flame retardancy grade is required to reach the UL94-V0 standard. Halogen-containing flame retardant materials release dioxins and other harmful substances that seriously threaten human health and the environment during combustion or heating. For this reason, the flame retardant used in the present invention is a halogen-free phosphorus-containing flame retardant, which avoids the shortcomings of the above-mentioned halogen-containing flame retardant materials.
[0223] In a preferred embodiment, the coupling agent is a vinyl silane coupling agent. The coupling agent acts as a bridge between the filler and the resin body in the material system of the present invention to increase its bonding ability. On the other hand, the present invention can change the fluidity of the composition solution by adding a coupling agent, increase the adhesion between the resin and the filler, and make the material system easy to impregnate the cloth; and can prevent the sag defect caused by the flow when the glue is applied too thick or too thin, thereby ensuring the uniformity of the impregnated cloth.
[0224] In a preferred embodiment, the accelerator is a peroxide catalyst. The accelerator in the present invention can reduce the curing temperature of the composition and improve the curing crosslinking degree.
[0225] In a preferred implementation, the solvent is a combination of one or more of toluene, xylene, butanone and cyclohexanone.
[0226] Through the above technical scheme, the resin composition of the present invention has the characteristics of extremely low XY axis expansion coefficient, dielectric constant, low dielectric loss and strong heat resistance.
[0227] Furthermore, the present invention also provides the following preparation examples 1-11 of the thermosetting resin composition, which is prepared based on the curable polyphenylene ether resins A1-A11 provided above. The specific examples are shown in the following table (the proportions of each raw material are calculated by weight):
[0228] Table 1 Raw material composition and ratio of the resin composition of Examples 1-11
[0229]
[0230]
[0231] Product tests on the resin composition of the present invention:
[0232] (1) Preparation of Comparative Examples 1-6, the raw material composition and proportion of each comparative example are shown in the following table:
[0233] Table 2 Raw material composition and ratio of the resin composition of Comparative Examples 1-6
[0234]
[0235]
[0236] (2) Preparation of samples to be tested:
[0237] The raw materials of Examples 1-11 and Comparative Examples 1-6 of the thermosetting resin composition were dissolved or dispersed in a solvent to obtain the adhesive of the resin composition of each example. The adhesive of each example was impregnated on the reinforcing material E-Glass of the same size and specifications, and baked in an oven at 120-160°C for 2-6 minutes to obtain a prepreg.
[0238] The six semi-cured sheets of each example were stacked, and a 1OZ copper foil was covered on the top and bottom to form a composite layer material. The composite layer material was placed in a vacuum laminator for pressing and maintained at 190°C*120min to obtain the copper clad laminate samples of the above-mentioned Examples 1-11 and Comparative Examples 1-6, so as to evaluate the characteristics of the copper clad laminates of each example.
[0239] (3) Test performance of copper clad laminate samples. The copper clad laminate samples obtained in (2) were tested. The test data are shown in Tables 3 and 4 below:
[0240] Table 3 Performance data of copper clad laminate samples prepared from Examples 1-11 of thermosetting resin compositions
[0241]
[0242]
[0243] Table 4 Performance data of samples of Comparative Examples 1-6
[0244]
[0245] From the sample test in Table 3 above, it can be seen that the copper clad laminate prepared using the resin composition of the present invention has excellent comprehensive performance, and has the characteristics of extremely low expansion coefficient, dielectric constant, low dielectric loss, and strong heat resistance. The Z-CTE of the copper clad laminates prepared in Examples 1-11 is lower than 1.3, and the X / Y axis CTE is lower than 9.1. And the copper clad laminate of Example 5 has the lowest comprehensive thermal expansion coefficient, with a Z-CTE of 1.0 and an X / Y axis CTE of 8.2.
[0246] Combining Table 3 and Table 4, it can be seen from the comparison between Example 1 and Comparative Example 1 that when the proportion of synthetic vinyl polyphenylene ether (number average molecular weight 800-1400) decreases and is less than 20 parts by weight, the X / Y axis CTE of the sample increases. It can be seen from the comparison between Example 8 and Comparative Example 2 that when the proportion of synthetic vinyl polyphenylene ether (number average molecular weight 800-1400) increases and is higher than 50 parts by weight, the X / Y axis CTE of the product increases significantly. It can be seen that there are obvious requirements for the proportion of synthetic vinyl polyphenylene ether (number average molecular weight 800-1400) in the resin composition, and excessive or too small amounts will lead to an increase in the X / Y axis CTE.
[0247] From the comparison between Example 3 and Comparative Example 3, it can be seen that when the number average molecular weight of the synthetic vinyl polyphenylene ether in the raw material is relatively large, the X / Y axis CTE increases significantly, the thermal expansion coefficient is relatively high, which affects the thermodynamic properties of the product and makes it difficult to meet the needs of high frequency and high speed for copper clad laminates with lower expansion coefficients.
[0248] From the comparison between Example 3 and Comparative Examples 4 and 5, it can be seen that when the synthetic vinyl polyphenylene ether in the raw material is replaced with the common PPO raw material in the industry, the X / Y axis CTE of the copper clad laminate is as high as 1.8, and the thermal expansion coefficient is relatively high. Comparative Examples 4 and 5 cannot have both low XY axis CTE and low dielectric properties, and it is difficult to meet the needs of high frequency and high speed for copper clad laminates with lower expansion coefficients.
[0249] By comparing Example 1 with Comparative Example 6, it can be seen that when the bismaleimide used in the raw material is difunctional diphenylmethane bismaleimide, the X / Y axis CTE of the product increases. To achieve a lower expansion coefficient, it is necessary to use multifunctional bismaleimide to increase the crosslinking density of the material and reduce the CTE.
[0250] The application of the resin composition of the present invention mainly includes the following:
[0251] (1) Preparation of prepreg:
[0252] First, the glue liquid of the resin composition is transferred to a glue tank; then, the reinforcing material is completely immersed in the glue tank under the action of a dipping roller, and in the glue tank, the glue liquid enters the interior of the reinforcing material to complete the dipping process; then, the reinforcing material after dipping is squeezed by adjusting the squeezing roller so that the glue content is 50-80% (mass percentage), and baked at a temperature of 120-190° C. for 2-5 minutes to obtain a prepreg;
[0253] In a specific implementation, the reinforcing material may be glass fiber cloth, aramid fiber cloth or non-woven fabric; the glass fiber cloth may be E glass cloth, D glass cloth, NE glass fiber cloth or quartz cloth, etc.
[0254] (2) Semiconductor devices:
[0255] The semiconductor device includes a cured product of the resin composition, or includes a sheet-shaped cured product of the prepreg. Specifically, the cured product of the resin composition can be an interlayer dielectric layer material.
[0256] Specifically, the semiconductor device also includes a chip, and the cured product of the resin combination is located between the chip and the chip. Generally, the interlayer dielectric layer material between the chip and the chip generally does not contain reinforcing materials. In addition, the cured product of the resin combination that does not contain reinforcing materials can also be a bottom filling glue material, a packaging material, a photoresist layer material, etc. in the semiconductor device. For another example, the cured product of the low-dielectric material and the sheet-like cured product of the above-mentioned prepreg can also be used in fields such as printed circuit boards (PCBs) as insulating resin materials for printed circuit boards.
[0257] (3) Printed circuit board:
[0258] The printed circuit board includes the sheet-like cured product of the above-mentioned semi-cured sheet. Specifically, the printed circuit board includes a laminate, also known as a copper-clad laminate. The laminate includes an insulating sheet and a metal foil located on one side or two opposite sides of the insulating sheet, wherein the insulating sheet includes at least one sheet-like cured product of the above-mentioned semi-cured sheet (which may be referred to as a "cured sheet"). That is, the insulating sheet may include a sheet-like cured product of the above-mentioned semi-cured sheet, or include at least two sheet-like cured products of the above-mentioned semi-cured sheets stacked together. In addition, the printed circuit board also includes a circuit arranged on the metal foil of the above-mentioned laminate.
[0259] In a specific implementation of the present invention, the above-mentioned laminate can be prepared by the following method:
[0260] Multiple prepregs are stacked together, copper foil is covered on both sides of the stacked prepregs, and then pressed together using a hot press to form a double-sided copper-clad copper laminate.
[0261] Through product testing, the glass transition temperature of the copper clad laminate prepared by the present invention is 200-230°C, the 5% thermal weight loss temperature Td is 410-430°C, and the XY axis thermal expansion coefficient is 8-9.5ppm / °C (refer to IPC-TM-650); 2116 cloth is tested at a frequency of 10GHz, the dielectric constant is 3.8-4.1 (refer to IPC-TM-650), the dielectric loss is 0.0044-0.0048 (refer to IPC-TM-650), and the flame retardant grade tested by the UL94 method is V0, which is particularly suitable for preparing high-speed circuit substrates.
[0262] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Therefore, any modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention shall still fall within the scope of the technical solution of the present invention.
Claims
1. A thermosetting resin composition, characterized in that The thermosetting resin composition comprises the following raw materials in parts by weight: 20-50 parts of curable polyphenylene ether resin; 10-30 parts of multifunctional bismaleimide resin; Containing 30-70 parts of benzene ring or heterocyclic vinyl crosslinking agent; 1 to 15 parts of flame retardant; 100-150 parts of filler; Accelerator 0.1-1 part; 0.1 to 1 part of vinyl-containing silane coupling agent; 50 to 100 parts of solvent.
2. A thermosetting resin composition according to claim 1, characterized in that: The structural formula of the curable polyphenylene ether resin is: Wherein, both R1 and R2 are curable functional groups containing a biphenyl structure, and the number average molecular weight of the curable polyphenylene ether resin is 800 to 1400 g / mol.
3. A thermosetting resin composition according to claim 2, characterized in that: R1 and R2 in the structural formula of the curable polyphenylene ether resin are independently selected from structural formula I or structural formula II; Structural formula I is: Structural formula II is: In the above structural formula I and structural formula II, R3, R4, R7, and R8 are each independently selected from a hydrogen group or a methyl group; R5, R6, R9, and R10 are each independently selected from a hydrogen group or a vinyl group; Among them, R5 and R6 are located at the ortho, meta or para position of the benzene ring, and R5 and R6 contain at least one vinyl group; R9 and R10 are located at the ortho, meta or para position of the benzene ring, and R9 and R10 contain at least one vinyl group.
4. A thermosetting resin composition according to claim 2, characterized in that: The structural formula of X in the structural formula of the curable polyphenylene ether resin is: The n is selected from an integer of 1-50, and the m is selected from an integer of 1-50.
5. A thermosetting resin composition according to claim 1, characterized in that: The multifunctional bismaleimide resin includes a bismaleimide monomer having at least three functional groups.
6. A thermosetting resin composition according to claim 1, characterized in that: The benzene ring or heterocyclic vinyl crosslinking agent is at least two of divinylbenzene, 4,4'-divinylbiphenyl, 4,4'-diallyl-1,1'-biphenyl, vinyl norbornene, 2,2-diallyl-4,4'-biphenol, and an unsaturated styrene-butadiene copolymer with a number average molecular weight of 800 to 2000 g / mol, triallyl isocyanate, and vinyl phosphazene; The filler comprises nano-spherical silicon and micron-spherical silicon, wherein the nano-spherical silicon accounts for 5% to 30% of the total weight of the filler, and the micron-spherical silicon accounts for 70% to 95% of the total weight of the filler.
7. A thermosetting resin composition according to claim 1, characterized in that: The thermosetting resin composition further comprises 0 to 6 parts by weight of core-shell rubber.
8. A method for preparing a thermosetting resin composition according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Step (1): dissolving the single-terminal polyphenylene ether PPO-OH in a solvent, stirring to obtain a solution, adding an initiator, a phenolic compound and an inhibitor to the solution for reaction; wherein the reaction temperature is 70 to 80° C., the reaction time is 5 to 7 hours, after the reaction is completed, precipitating with a poor solvent for the polyphenylene ether, and then filtering and washing to obtain the double-terminal hydroxyl polyphenylene ether PPO-2OH; Wherein, the molecular structural formula of the phenolic compound is Step (2): at 60° C., dissolving the double-terminated hydroxyl polyphenylene ether PPO-2OH obtained in step (1) in toluene to obtain a polyphenylene ether solution, stirring, adding dichloromethane to a 10 wt % NaOH solution to obtain an alkaline solution; then, in a nitrogen environment, adding the alkaline solution to the polyphenylene ether solution for reaction for 0.5 h, and then adding tetrabutylammonium bromide; finally, slowly adding a dichloromethane solution containing a capping agent to the polyphenylene ether solution for reaction; extracting the product after the reaction with ethanol for 4 to 5 times, and then filtering and vacuum drying for 10 h to obtain a vinyl-terminated biphenyl curable polyphenylene ether; Wherein, the molecular structural formula of the end-capping agent is 9. A prepreg, characterized in that: Prepared by the thermosetting resin composition according to any one of claims 1 to 7.
10. A printed circuit board, characterized in that: The printed circuit board includes a laminate, the laminate includes an insulating sheet, and metal foils located on one side or opposite sides of the insulating sheet, and the insulating sheet includes at least one prepreg according to claim 9.
Citation Information
Cited By
Laminating, printing and glue filling process for multi-layer thick copper plate
CN121357823A